2017
DOI: 10.1007/s11010-017-2978-0
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific protease 14 regulates LPS-induced inflammation by increasing ERK1/2 phosphorylation and NF-κB activation

Abstract: Persistent activation of nuclear factor B (NF-κB) is very important in the modulation of macrophages cellular response to microbial infections. The deubiquitinase USP14, which is critical for ubiquitin-mediated proteasomal degradation of proteins, is known to be involved in cancer, neurological diseases, and aging. However, the mechanism by which USP14 regulates inflammation remains unclear. Here, we demonstrated that decreasing the deubiquitinase activity of USP14 resulted in reduced lipopolysaccharides (LPS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 30 publications
4
36
0
Order By: Relevance
“…Usp14 activity is elevated in LPS-treated-cells, in parallel with its phosphorylation, possibly by AKT [74,75]. These and other observations suggest an anti-inflammatory effect of Usp14 inhibition [7478]. …”
Section: Enzymatic Activity and Its Regulationmentioning
confidence: 88%
See 1 more Smart Citation
“…Usp14 activity is elevated in LPS-treated-cells, in parallel with its phosphorylation, possibly by AKT [74,75]. These and other observations suggest an anti-inflammatory effect of Usp14 inhibition [7478]. …”
Section: Enzymatic Activity and Its Regulationmentioning
confidence: 88%
“…Experiments in various model systems have revealed a multitude of processes in which Usp14 and Ubp6 may function [3133,45,47,48,50,7678,90,91,93,109,113,127138]. An interesting phenotype of ubp6 null mutants in yeast is their exceptional and perhaps unique ability to tolerate aneuploid chromosomes [135137].…”
Section: Physiological Functionmentioning
confidence: 99%
“…Our previous studies have shown that USP14 stabilizes AR protein expression by removing the K48 ubiquitin chain on AR in prostate cancer cells and breast cancer cells. Moreover, except for in cancer cells, we also found that USP14 regulates the progression of cardiac hypertrophy via promoting GSK‐3β phosphorylation and USP14 mediates LPS‐induced inflammation by activating ERK1/2 and NF‐κB pathways . However, the function of USP14 in the development of atherosclerosis remains unknown.…”
Section: Discussionmentioning
confidence: 86%
“…USP14 can reduce the anchoring time of ubiquitin conjugates and stabilize the proteins via inducing deubiquitination of proteins . Moreover, in our previous study, we have reported that USP14 was involved in inflammatory diseases by increasing ERK1/2 phosphorylation and NF‐κB activation …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation